Febrile neutropenia in cancer patients: a literature review - Limberger, Luana Medeiros; Bonfim Filho, Jair Alves (Research, Society and Development, 2023)
Introduction: Febrile neutropenia is currently a frequently observed condition in the oncology therapy setting. This complication is associated with the use of chemotherapy. Objective: to contribute to the continuous reduction of mortality associated with this condition, through an approach focused on risk stratification and early broad-spectrum antibiotic therapy. Method: A narrative literature review was performed using the Pubmed, Scielo and UptoDate databases. For the search, the descriptors were used: "Febrile Neutropenia"; "Neutropenia in cancer patients"; "Post chemotherapy fever" and "Febrile post chemotherapy neutropenia". The guiding question was: “What risk stratification and treatment are most appropriate for cancer patients with febrile neutropenia?”. Articles between the years 2010 to 2023 were selected. Articles that did not respond to the guiding question were excluded. 237 articles were found, of which 34 matched the pre-established criteria. Results and Discussion: Fever is commonly reported in cancer patients undergoing chemotherapy. In most cases the infectious focus is not found. Individuals with febrile neutropenia are classified according to the severity of the clinical condition, intensity of neutropenia and according to the chemotherapy regimen used. Early recognition and initiation of empirical antibiotic therapy are essential for a good prognosis. It is concluded that adequate risk stratification, diagnosis and therapy in a short period of time lead to a reduction in mortality.